An Empirical Study of Factors Affecting Organizational Commitment in Banking Sector - Chhabra, IP; Lalwani, H; Gupta, B; Hyde, AM; Kashyap, V (International Journal of Computer Sciences and Engineering, 2025)
Organizational Commitment refers to the employee’s emotional attachment to, identification with, and involvement in a particular organization. It today’s globalised world it become very difficult to retain talented employees. Organizations often try to foster commitment in their employees to achieve stability and reduce costly turnover. This research helps in exploring the key factors which contributes in predicting Commitment level of employees working in banking sector. Data were collected from 100 managerial and non-managerial employees of Private and Public Sector Banks using convenient sampling. Factor Analysis was used to identify the factors which are contributing in Organizational Commitment. Factor analysis was adopted to capture the factors that affect Organizational commitment of Managerial and Non managerial employees of Bank employees. The result of the study reveals that employees are not much concerned about ‘flexibility in management style’. Their focus is mainly on ‘job security’. The outcome of this research is beneficial for policymakers, planners and development economists to formulate effective strategy of human resource development in Banking sector and other similar sectors.